Employee Retention Management Strategy and Mitigating Resistance to Change in the Adoption of Artificial Intelligence (AI) in the Corporate Sector - Yeti Yeti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The accelerated adoption of Artificial Intelligence (AI) technology in the corporate sector has triggered massive structural transformation while simultaneously generating deep anxiety among the workforce regarding disruption and job substitution. This study aims to formulate employee retention management strategies and mitigate resistance to change during the AI ​​integration process in the corporate environment. Using empirical normative legal research methods through a conceptual approach and analysis of organizational behavior management literature, this article dissects the root causes of employee resistance and the effectiveness of various managerial interventions. The analysis results indicate that employee resistance is not inherent to the technology itself, but rather is triggered by fear of job loss (job insecurity), minimal communication transparency, and digital competency deficits. This study concludes that the implementation of upskilling programs, the application of participatory communication, and the adoption of a human-based change management framework such as the ADKAR model can reduce employee turnover rates, align human-machine synergy, and ensure the sustainability of company operations in the era of automation.